An integrated protocol based on workflows of imaged capillary isoelectric focusing (icIEF) for in-depth protein heterogenous characterization: High-efficient fractionation and online mass spectrometry detection - Teresa Kwok; She Lin Chan; Mike Zhou; Tong Chen; Niusheng Xu; Victor Li; Tiemin Huang; Tao Bo (Green Analytical Chemistry)
We present an integrated protocol for studying the charge heterogeneity of therapeutic proteins combining two workflows: imaged capillary isoelectric focusing (icIEF) with fractionation and online mass spectrometry (MS) detection on a single platform. This protocol enables both intact MS-based protein charge variant characterization and in-depth peptide mapping of collected fractions via high-performance liquid chromatography (HPLC) tandem mass spectrometry. Through systematic methodology validation, the platform is demonstrated to be robust, with step-by-step method development, standardized operating procedures (SOPs), exceptional reproducibility, and high sensitivity. Notably, this protocol facilitates icIEF-UV separation followed by either a fractionation scheme or MS online detection within a single platform, providing simplified workflows with reduced reagent consumption compared to traditional techniques. Embracing the ''Green Chemistry'' concept, the protocol addresses key challenges in biopharmaceutical discovery, quality control, and manufacturing, promoting sustainability throughout the process.